Research on Identification Model of Continuous Compaction Based on Energy Dissipation - Longliang Wu; Jun Teng; Zhenyang Ren; Huihuang Jiang; Mingxian Gao (Shock and Vibration)
A continuous compaction control energy model suitable for contact decoupling between the vibrating wheel and the filling body surface is established through analyzing the energy state of the filling body in the compaction detection stage and calculating nonlinear vibration energy dissipation rate based on the basic principle of continuous compaction control technology and the principle of energy conservation. The significance of the parameters contained in the energy model is analyzed, and the energy index-dissipation measured value (DMV) for evaluating the continuous compaction quality is put forward in combination with engineering practice. The feasibility of DMV is verified, and the applicability of DMV is discussed according to the field test results. The results show that the variation range of the DMV index is about 1.66–2.73 times of the Evd index, the DMV has good repeatability and sensitivity for both coarse-grained and fine-grained filler, and it is less affected by the interference caused by the small fluctuation of mechanical parameters, and has good stability for the local unevenness of filler in horizontal direction. The engineering application shows that the correlation coefficient between energy index DMV and Evd index reach more than 0.87, there is a good correlation between DMV and the conventional quality inspection index Evd, indicating that the energy model is applicable.